The expressive function of borders in otia ioseliani's prose - Pilashvili, Elene (The International tax journal, 2024)
The author’s focus is on unexpected word combinations and the emotional weight of delimiters conveyed by abstract nouns. These abstract nouns typically correspond to specific nouns but are infused with artistic tone and heightened expressiveness. The striking word gains artistic value through a carefully chosen modifier, imbuing it with an element of surprise and added expressiveness. For instance, the word fear typically evokes a negative emotion in the reader; however, the writer pairs it with words that carry positive semantics, giving it a unique, expressive quality: 'This is both fear and not fear, beautiful fear, good fear' (Ioseliani, 2010: 277).